The relationship between physical activity levels and health-related quality of life in elderly individuals aged 65 years and above with a chronic disease - NEVZAT DEMIRCI; PERVIN TOPTAŞ DEMIRCI; OKTAY ZIRHLI (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: Chronic diseases are the leading cause of death worldwide with increasing prevalence in the population aged 65 years and above. This study aimed to evaluate the relationship between physical activity level and health-related quality of life in elderly individuals. Material and methods: The participants aged 65 years and older (46 males and 35 females) were divided into 3 groups according to their physical activity levels: low physical activity (<150 minutes/week), moderate physical activity (150-300 minutes/week) and high physical activity level (>300 minutes/week). Health-related quality of life (HRQoL) was calculated using EQ-5D scale. Spearman's correlation coefficient was used to determine the relationship between physical activity level and HRQoL scores in elderly individuals. Results: A significant relationship and differences were found between high, moderate and low physical activity levels and HQQoL dimensions (P<0.05). The moderate and high physical activity groups were found to be significantly higher in all dimensions compared to the low physical activity group according to HRQoL scores (P<0.001). Conclusions: It has been concluded that high and moderate physical activity levels have a great positive relationship with HRQoL in individuals aged 65 years and older with a chronic disease.